Factors Governing Clutch Size in Two Species of Diaptomus (Copepoda: Calanoida) - Chow-Fraser P; Maly EJ (Canadian Science Publishing, 1991)
Some 60% of the variation in clutch size of Diaptomus minutus could be accounted for by temperature and while 80% of the variation in the D. oregonensis data was explained by temperature and prosome length. D. minutus in sympatry may have lower clutch size than those in allopatry when temperature and food concentration were held constant. Clutch size decreased significantly in relation to food limitation for both species, but was unaffected by mate limitation. -from Authors
Keywords: 3109 Zoology; 3103 Ecology; 31 Biological Sciences